Method for producing electrode, electrode, dry coating composition, battery, and electronic circuit
Patent Information
- Application Number
- JP2023577630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-16
- Filing Date
- 2022-06-07
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2042-06-07
AI Technical Summary
Existing electrode manufacturing methods for ion batteries, such as lithium ion batteries, involve the use of harmful solvents and can result in bubble formation and poor contact between the current collector substrate and active material, especially in thicker electrodes, posing health and environmental risks.
A dry coating method using a free-flowing powder coating composition is applied to a conductive substrate, which can be a porous material with a three-dimensional network of metal fibers, allowing for solvent-free manufacturing and improved penetration into substrate pores, followed by heating and optional compression to form the electrode.
This method reduces environmental impact, enhances electrode performance by minimizing solvent use, and enables the production of thicker electrodes with improved contact and conductivity, resulting in higher energy density and stability.
Smart Images

Figure 00000015_0000 
Figure 00000015_0001 
Figure 00000015_0002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an electrode, and to an electrode, a dry coating composition, a battery, and an electric circuit. [Background technology]
[0002] Ion batteries, such as lithium-ion batteries, typically have electrodes that are fabricated by dispersing powdered active material in a solvent. The dispersion is doctor bladed onto a current collector substrate, typically a metal foil, and then dried to obtain the electrode. Such coating processes require the utilization of solvents that are harmful to health and / or the environment.
[0003] Furthermore, for thicker layers of active material, which are desirable for providing thick electrodes and enabling higher battery energy areal densities, applying the active material as a dispersion onto the current collector substrate can result in several drawbacks due to the drying process in which the solvent of the dispersion evaporates, as described, for example, by Kuang et al. in “Thick Electrode Batteries: Principles, Opportunities, and Challenges”, Adv. Energy Mater. 2019, 9, 1901457. In particular, if the drying process is too rapid, it can result in the formation of air bubbles and poor contact between the current collector substrate and the active material. Summary of the Invention
[0004] In view of the above, there is a need for a method of manufacturing an electrode that overcomes the above-mentioned problems. [Means for solving the problem]
[0005] The present invention solves these problems by a method according to claim 1, an electrode according to claim 10, a coating composition according to claim 12, a battery according to claim 14 and a circuit according to claim 15.
[0006] The present invention relates to a method for producing an electrode, comprising the steps of: (A) providing a conductive substrate; (B) providing a coating composition comprising an electrode active material and optionally a binder, said coating composition being a free-flowing powder; (C) coating the conductive substrate provided in step (A) with the coating composition provided in step (B); and (D) heating the coated conductive substrate obtained in step (C) and optionally compressing the coated conductive substrate (14), such as by calendaring.
[0007] The coating process utilizes a dry coating composition that is a free-flowing powder. It is more efficient in cost and chemical consumption since no solvent is required to create a dispersion. In principle, these advantages can be realized for any kind of conductive substrate. The conductive substrate can be a current collector substrate. The method of the present invention is particularly suitable for producing three-dimensional (3D) electrodes. The free-flowing powder can easily penetrate cavities and pores, such as porous conductive substrates. As the coating composition is a free-flowing powder, no evaporation of the solvent is required, simplifying the manufacturing process.
[0008] In conjunction with the embodiment of a three-dimensional fiber network electrode, methods of manufacturing battery electrodes of various thicknesses are described herein, however, the invention is not limited to three-dimensional fiber networks and may be implemented using other conductive substrates.
[0009] According to the present invention, the conductive substrate prepared in step (A) is preferably a porous conductive substrate. By using a free-flowing powder as the coating composition, the pores of such a porous conductive substrate can be easily penetrated, and a thick electrode can be produced.
[0010] From the viewpoint of using the porous conductive substrate, the pores of the porous conductive substrate are preferably in the range of 0.1 to 2000 μm. The range of 0.1 to 2000 μm refers to the average average pore diameter. More preferably, it is in the range of 0.5 to 1000 μm, more preferably in the range of 1 to 1000 μm, even more preferably in the range of 2 to 500 μm, and even more preferably in the range of 5 to 500 μm. The average average pore diameter can be determined by reproducing the 3D structure of the porous conductive substrate using a microcomputer tomograph, and then evaluating the average pore diameter using the bubble point method. The bubble point method determines the maximum ball diameter that can fit into the cavity of the porous substrate, which is considered to be the pore diameter. More specifically, a point is placed in the center of the cavity of the conductive substrate, for example between two fibers, and the radius of the bubble is increased around the point until it touches each surface adjacent to the cavity of the conductive material, for example both fibers. The diameter of the bubble corresponds to the pore diameter. If for any given parameter the bubble diameter only touches one surface, e.g. one fiber, then the center point is shifted towards the surface, e.g. fiber, that the bubble did not touch.
[0011] The porosity of the conductive substrate, especially when it comprises or consists of a three-dimensional network of metal fibers, is preferably in the range of 95% to 99.5% by volume, especially in the range of 96% to 99.4% by volume, and especially in the range of 97% to 99.0% by volume. Such high porosity allows the addition of a large amount of electrode active material, reducing the proportion of inactive components, thereby improving the battery performance per mass. The porosity can be determined by reproducing the fiber structure using a microcomputer tomograph and then evaluating the porosity using the bubble point method described herein.
[0012] The conductive substrate is not particularly limited. The present invention can be realized with many different conductive substrates. Particular advantages can be realized especially when the conductive substrate has a three-dimensional structure, such as a woven fabric, a nonwoven fabric, or a form of a network of fibers. The fibers should have sufficient electrical conductivity, such as carbon nanotubes or graphite fibers or metal fibers. The electrical conductivity of the conductive substrate is 10 5The electrical conductivity is preferably 1.0 S / m or more. The upper limit is not particularly limited and is determined by the material and structure of the conductive substrate.
[0013] According to the present invention, the conductive substrate prepared in step (A) preferably comprises a plurality of metal fibers forming a network of metal fibers. These metal fibers provide the conductive substrate with a porous structure, the pores of which can be easily filled with the free-flowing powder coating composition in step (C). The metal fibers provide high electrical conductivity and a high surface area on which the electrode active material can be deposited. This allows the mass of the substrate relative to the mass of the active material to be kept low, resulting in a high energy density.
[0014] In the conductive substrate prepared in step (A), it is preferable that the metal fibers forming the network are in direct contact with each other, which improves the conductivity of the entire conductive substrate even when the conductive substrate is very thick.
[0015] Preferably, the thickness of the conductive substrate prepared in step (A), especially when it has a three-dimensional structure, is 200 μm or more, more preferably 500 μm or more, even more preferably 550 μm or more, even more preferably 600 μm or more, even more preferably 750 μm or more, even more preferably 1000 μm or more, even more preferably 1500 μm or more, even more preferably 3000 μm or more, and most preferably 5000 μm or more. The thickness of the conductive substrate, especially when it has a three-dimensional structure, is not particularly limited. It may be 10 mm or less, preferably 8 mm or less, more preferably 5 mm or less, and even more preferably 3 mm or less.
[0016] The number of contact points between the metal fibers constituting the conductive substrate prepared in step (A) can vary within a wide range. Preferably, the density of the contact points is less than 1 mm -3 ~5000mm -3 More preferably, the density of the contact points is in the range of 3 mm -3 ~2000mm -3 , and more preferably 5 mm -3 ~500mm-3 The density of contact points can also be considered as the bridge density between the fibers, especially when the metal fibers are fixed to each other at the contact points, i.e., when the metal fibers are fixed directly to each other and are in electrical contact with each other at the contact points. -3 Above, especially 5mm -3 A contact density of 5000mm or more provides a uniform distribution of potential and avoids harmful effects such as high overvoltages or localized hot areas due to high resistance. -3 Below, especially 2000mm -3 Below, more specifically, 500mm -3 The following contact point densities are useful for imparting flexibility to the three-dimensional network of metal fibers forming the conductive substrate, so that even fairly thick three-dimensional networks, i.e., thicknesses of 200 μm or more, 500 μm or more, or 550 μm or more, or 600 μm or more, or 750 μm or more, can be deformed, e.g., rolled, without destroying the network.
[0017] It is also preferred that the volume fraction of the metal fibers in the conductive substrate, in particular the three-dimensional network of metal fibers, is 0.075 vol.% or more, in particular 1.3 vol.% or more, in particular 2.0 vol.% or more. In networks with lower volume fractions, it may be difficult to distribute the local potential uniformly, which may result in the formation of hot spots and high overvoltages. Thus, the volume fraction of the metal fibers in the three-dimensional network of metal fibers specified above can extend the battery life. The volume fraction of the metal fibers in the three-dimensional network of metal fibers can be determined by reproducing the fiber structure using a microcomputer tomograph and then evaluating the fraction using the bubble point method described herein.
[0018] The conductive substrate provided in step (A), in particular when it comprises or consists of a three-dimensional network of metal fibers, has a conductivity of 1×10 5 S / m or more, especially 5×10 5 S / m or more, especially 1×10 6It is particularly preferred that the porosity is in the range of 95 vol.% to 99.5 vol.%, particularly in the range of 96 vol.% to 99.4 vol.%, and in particular in the range of 97 vol.% to 99.0 vol.%, and that the volume fraction of the metal fibers in the three-dimensional network of the metal fibers is 0.075 vol.% or more, particularly 1.3 vol.% or more, and in particular 2.0 vol.% or more.
[0019] Preferably, in the conductive substrate, the fibers, especially the metal fibers, are in direct electrical contact with each other so as to maximize electrical conductivity. In this regard, it is particularly preferred that all metal fibers are sintered to other metal fibers, most preferably directly sintered to other metal fibers, without the need for additional binders, such as polymer binders or solders. Thus, it is even more preferred that the metal fibers are fixed to each other without a polymer binder, since such polymer binders often have poor electrical conductivity and high temperature performance.
[0020] It may be preferred that the metal fibers include at least one of copper, silver, gold, nickel, palladium, platinum, cobalt, iron, chromium, vanadium, titanium, aluminum, silicon, lithium, manganese, boron, combinations of the above, and alloys containing one or more of the above, such as CuSn8, CuSi4, AlSi1, Ni, stainless steel, Cu, Al, or Vitrovac alloy. Vitrovac alloy is an amorphous alloy based on Fe and Co. It may be particularly preferred that the metal fibers are made of copper or aluminum or stainless steel alloy. Different types of metal fibers can be combined with each other, so that the conductive substrate can include, for example, metal fibers made of copper, one or more stainless steel alloys, and / or aluminum. It is particularly preferred that the network is made of metal fibers consisting of copper, aluminum, cobalt; stainless steel alloys containing copper, aluminum, silicon, and / or cobalt.
[0021] The fibers can be sintered together, for example as described in WO 2020 / 016240 A1.
[0022] According to the present invention, the metal fibers of the conductive substrate prepared in step (A), before being fixed together, preferably exhibit an exothermic event when heated in a DSC measurement, the exothermic event releasing energy in an amount of 0.1 kJ / g or more, more preferably 0.5 kJ / g or more, even more preferably 1.0 kJ / g or more, and most preferably 1.5 kJ / g or more. The absolute amount depends very much on the metal or metal alloy used. The extent of the exothermic event can be determined by comparing the DSC measurements of the metal fibers before and after thermal equilibrium. In other words, metal fibers exhibiting such an exothermic event are not in thermodynamic equilibrium at ambient temperature. During heating in a DSC measurement, the metal fibers may transition from a metastable state to a thermodynamically more stable state, such as by crystallization, recrystallization, or other relaxation processes that reduce defects in the lattice of metal atoms. Exothermic events observed in metal fibers when heated, such as during DSC measurements, indicate that the metal fibers are not in thermodynamic equilibrium, e.g., the metal fibers may be in an amorphous or nanocrystalline state that contains defect energy and / or crystallization energy that is released during heating of the metal fibers by crystallization or recrystallization occurring. Such events can be recognized, such as using DSC measurements. Networks of metal fibers that exhibit such exothermic events have been found to have enhanced strength after the metal fibers are fixed together.
[0023] Optionally, the metal fibers of the conductive substrate have a non-circular cross section, in particular a rectangular, square, partially circular, or elliptical cross section with a major axis and a minor axis. Such cross sections usually result in fibers that are not in thermal equilibrium, i.e., in a metastable state, which may be beneficial in some applications. The non-circular cross section further increases the surface area per mass of the metal fibers, thereby also contributing to the performance of the electrode per mass.
[0024] In this connection, it is clearly noted that the value of the minor axis must be smaller than the value of the major axis. If the minor axis has a larger value than the major axis, i.e. a longer length, then the definitions of "short" and "long" must simply be interchanged.
[0025] It may be preferable that the ratio of the minor axis to the major axis is in the range of 1 to 0.05, preferably in the range of 0.7 to 0.1, in particular in the range of 0.5 to 0.1. As is generally known, the ratio of the length of the minor axis to the major axis of an ellipse is so large that the ellipse looks more like a circle, in which case the ratio would be 1. The smaller the value of the ratio, the flatter the ellipse. The ratio of the minor axis to the major axis is therefore in particular less than 1.
[0026] Alternatively, metal fibers can have a circular cross section. In such a cross section, the ratio of the "long" axis to the "short" axis would obviously be exactly 1. A circular cross section has a more energetically favorable state than a cross section with an aspect ratio less than 1. Thus, a fiber with a circular cross section is closer to energetically equilibrium than a fiber with a cross section of any other shape.
[0027] Preferably, the metal fibers of the conductive substrate are formed by melt spinning the molten material of the metal fibers, in particular by vertical or horizontal melt spinning. 2 Kmin -1 Such metal fibers produced by melt spinning may contain spatially limited regions of a high energy state (i.e., a metastable state) due to the rapid cooling applied during the melt spinning process. Rapid cooling in this context means a cooling rate of 10 2 K.min -1 More than 10, preferably 4 K.min -1 More than 10, more preferably 5 K.min -1 The cooling rate refers to the above cooling rate. Therefore, the step (A) of preparing a conductive substrate preferably includes the production of metal fibers as described above and the formation of a network of the metal fibers.
[0028] Also, in the case of the conductive substrate prepared in step (A), the fibers obtained by melt spinning often have a rectangular or semi-elliptical cross section, which is far from the equilibrium state and is therefore preferred in certain application fields. Examples of melt spinning machines capable of producing such fibers are known, for example, from the yet unpublished international application PCT / EP2020 / 063026 and published applications WO2016 / 020493A1 and WO2017 / 042155A1, which are incorporated herein by reference.
[0029] According to another example, at least some of the metal fibers of the plurality of metal fibers are amorphous or at least some of the metal fibers of the plurality of metal fibers are nanocrystalline. Nanocrystalline metal fibers include crystalline regions. Upon heating to a temperature of about 20-60% of the melting point of the nanocrystalline metal fibers, these regions undergo recrystallization, resulting in an increase in the average size of the crystalline regions compared to the average size of the initial crystalline regions in the nanocrystalline metal fibers before heating. It is also possible to mix non-equilibrated fibers (e.g., nanocrystalline or amorphous fibers) with equilibrated fibers (e.g., annealed fibers).
[0030] The metal fibers preferably contained in the conductive substrate prepared in step (A) may preferably have a length of 1.0 mm or more and / or a width of 100 μm or less and / or a thickness of 50 μm or less. With metal fibers having such dimensions, it is possible to produce a network in which the metal fibers are fixed to one another without the need to heat the metal fibers to a temperature close to their melting point for a time period of more than 30 minutes. Conventional connection techniques, such as sintering or welding or mixing techniques, require a temperature close to or slightly above the melting point of the metal to be maintained for a relatively long time. This may cause the material of the metal fibers to melt or at least soften to some extent, so that the metal fibers form a metal foil rather than a network, especially when a relatively high pressure is applied during sintering. Since the network of metal fibers is not a metal foil, i.e. the structure of the metal fibers used to produce the network of metal fibers is still discernible in the network of metal fibers. Thus, in a cross-sectional view of the network of metal fibers, there are voids that are not part of the metal fibers but are between the metal fibers of the network fiber.
[0031] The width of the metal fiber is preferably 80 μm or less, more preferably 70 μm or less, even more preferably 40 μm or less, and most preferably 10 μm or less, and the thickness of the metal fiber is preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, and most preferably 5 μm or less.
[0032] For step (A), as described above, it is preferred to provide the conductive substrate on a support, especially when the conductive substrate has a porous structure. The support prevents the free-flowing powder from flowing through the conductive substrate, so that its pores or cavities can be filled with the coating composition. The support is not particularly limited. Preferably, the support is a non-stick support so that it can be easily removed after carrying out step (D). In addition, the support should be thermally stable under the conditions of step (D). Thermally stable in this context means that the support does not melt or decompose when carrying out step (D). That is, the support does not adhere to the conductive substrate and the electrode active material after carrying out step (D). The support may be, for example, siliconized paper, a polymer sheet, a metal foil, or a non-woven or woven sheet of fibers (e.g., natural fibers).
[0033] According to the present invention, in the step (B) of preparing the coating composition, it is preferred to mix the electrode active material, optionally a polymer binder, and optionally a conductivity enhancing additive (e.g., carbon black) to obtain the coating composition as a free-flowing powder. The coating composition may include the electrode active material, the polymer binder, and the conductivity enhancing additive (e.g., carbon black).
[0034] It is particularly preferred that the coating composition prepared in step (B) has a particle size smaller than the average mean pore size described above for the porous conductive substrate prepared in step (A). The particle size is preferably 80% or less, more preferably 50% or less, even more preferably 30% or less, and most preferably 20% or less, compared to the average mean pore size. The particle size of the free-flowing coating composition can be determined by commonly applied methods such as laser diffraction or sifting.
[0035] The coating composition prepared in step (B) preferably contains a polymer binder as a binder. The polymer binder is not particularly limited and may be a fluorine-containing polymer, carboxymethyl cellulose, styrene butadiene rubber, or other rubber. The binder, particularly the polymer binder, may be preferably contained in an amount of 0 to 30% by weight of the coating composition, more preferably 0.5 to 20% by weight of the coating composition, even more preferably 1 to 15% by weight of the coating composition, and even more preferably 1.5 to 7% by weight. Such a fluorine-containing polymer binder has excellent electrochemical stability and can improve the adhesion between the electrode active material and the conductive substrate. Suitable examples of the fluorine-containing polymer binder include poly(vinylidene fluoride) (PVDF) and poly(tetrafluoroethylene) (PTFE), but other polymer binders can also be used. It is also possible to use PVDF derivatives such as PVDF-HFP (poly(vinylidene fluoride-co-hexafluoropropylene)) or PTFE derivatives. However, it is also possible to realize the invention without a binder or with other binders. By avoiding the use of solvents, the risk of binder decomposition is reduced, which allows the use of many different types of polymers as binders. In this context, the polymer binder is preferably thermoplastic.
[0036] Preferably, the glass transition temperature and / or melting point, in particular the melting point, of the polymeric binder is above 30°C, more preferably above 50°C, even more preferably above 70°C. If the glass transition temperature and / or melting point is above the above temperatures, the polymeric binder is non-sticky at room temperature, which allows the preparation of a free-flowing powder in step (B) without the use of an anti-caking agent. The glass transition temperature (Tg) and melting point (Tm) of the polymeric binder can be measured using differential scanning calorimetry (DSC). During operation, secondary batteries, such as lithium-ion batteries, can heat up. The glass transition temperature and / or melting point in the above range can prevent extensive softening and flow of the binder during battery operation, which can then extend the life of the corresponding battery.
[0037] In step (B) of the method according to the invention, it is preferred to provide an electrode active material capable of intercalating monovalent or polyvalent ions, in particular lithium ions.
[0038] Preferably, in step (B) of the method according to the invention, the coating composition is prepared by mixing the components of the composition such that the electrode active material constitutes up to 100% by weight of the coating composition, more preferably up to 99% by weight of the coating composition, more preferably 70-99% by weight, even more preferably 80-98% by weight, and most preferably 80-95% by weight. By using a porous conductive substrate, in particular a network of metal fibers, it is possible to use very large amounts of electrode active material, since the use of binders and conductivity enhancing additives can be minimized. Thus, when using a porous conductive substrate, the coating composition is prepared by mixing the components of the composition such that the electrode active material constitutes preferably 80-100% by weight of the coating composition, more preferably 90-100% by weight of the coating composition, even more preferably 95-100% by weight of the coating composition, even more preferably 98-100% by weight of the coating composition, even more preferably 99-100% by weight of the coating composition, and most preferably 100% by weight of the coating composition. Also, a particularly preferred range is 95-98% by weight of the coating composition.
[0039] According to a preferred embodiment, the electrode active material is at least one selected from the group consisting of graphite, graphene, silicon, silicon carbide (SiC) and tin oxide (SnO), tin dioxide (SnO2) and lithium titanium oxide (LTO), or a mixture thereof. In another embodiment, the electrode material is a mixture of graphite and at least one selected from the group consisting of graphene, silicon, silicon carbide (SiC) and tin oxide (SnO), tin dioxide (SnO2) and lithium titanium oxide (LTO), in particular a mixture of graphite and silicon and / or silicon carbide. This is particularly preferred when the electrode produced by the method of the present invention is utilized as the anode of a monovalent or polyvalent ion battery, in particular a lithium ion battery.
[0040] According to another preferred embodiment, the electrode active material is at least one selected from the group consisting of lithium nickel manganese cobalt oxide (NMC), lithium nickel manganese oxide (NMO), lithium nickel cobalt aluminum oxide (NCA), lithium cobalt oxide (LiCoO2) and lithium iron phosphate (LFP), which is particularly preferred when the electrode produced by the method of the present invention is utilized as the cathode of a monovalent or polyvalent ion battery, in particular a lithium ion battery.
[0041] Whether the electrode produced according to the invention is intended to be utilized as a cathode or an anode of a battery, as described above, the electrode active material preferably comprises graphite that has been thermally pretreated, i.e. calcined. It has been found that heat treatment of the graphite renders it free-flowing, i.e. non-sticky. For example, the heat treatment can be carried out by heating to 1000° C. or higher under a protective gas atmosphere (such as argon) or in a vacuum. Without being bound by theory, it is assumed that the thermal pretreatment reduces the number of surface hydroxide groups and therefore the affinity for water. This in turn improves the free-flowing behavior of the graphite. If the electrode produced is intended for an anode, the graphite may be the majority or the entire electrode active material and may constitute up to 100% by weight of the coating composition. Alternatively, it may be used together with another suitable anode electrode active material, such as those listed above. If the electrode produced is intended for a cathode, the graphite is preferably present in an amount of up to 20% by weight of the coating composition, more preferably up to 10% by weight of the coating composition, and even more preferably up to 5% by weight of the coating composition. While there is no particular restriction on the minimum amount of graphite to be used in the cathode electrode active material, it may be preferred to utilize at least 0.5% by weight of the coating composition, and more preferably at least 1.0% by weight of the coating composition, to obtain certain improvements in the free-flowing behavior of the coating composition.
[0042] Also, in the step (B) of the method according to the present invention, when preparing the coating composition, it is preferred that a conductivity enhancing additive, such as carbon black, more preferably conductive carbon black, is included therein. Such carbon black can reduce the internal resistance of the final electrode. Such conductive carbon black is available, for example, as Super-P carbon black. In the method according to the present invention, the amount of such conductive carbon black is usually less than 10% by weight of the coating composition, more preferably less than 8% by weight of the coating composition, and even more preferably less than 6% by weight of the coating composition. In order to fully exert the effect of the conductivity enhancing additive (e.g. carbon black), it is preferred to include it in an amount of at least 0.2% by weight of the coating composition, more preferably at least 0.5% by weight of the coating composition, and even more preferably at least 1.0% by weight of the coating composition.
[0043] In the method of the present invention, step (B) of mixing the components of the coating composition is not particularly limited and can be realized by various mixing operations such as mixing by stirring, shaking, grinding (e.g. grinding in a mortar), milling (e.g. ball milling), etc. The mixing in step (B) is terminated when the components are mixed uniformly. When the electrode active material comprises or consists of graphite, it is preferred to mix the graphite and optionally other components by milling, in particular ball milling, in order to activate the graphite. According to the present invention, in step
[0044] In the method according to the invention, the coating composition prepared in step (B) is dry, i.e. essentially free of water and other solvents. This allows the coating composition to be prepared as a free-flowing powder, which can be easily distributed on the conductive substrate and enter structures provided thereon, such as pores or other cavities. Furthermore, evaporation of water or other solvents is not required.
[0045] Step (C) of the method according to the invention preferably comprises filling the pores or cavities of the conductive substrate provided in step (A) with a free-flowing coating material.
[0046] Filling of such pores or cavities can be accomplished by a variety of methods. As one example, a free-flowing powder can be sprinkled onto / into the conductive substrate. As another example, the coating composition can be sprayed onto / into the conductive substrate using a conventional or electrostatic sprayer.
[0047] In order to improve the filling of pores and cavities, in step (C) of the method according to the invention, it may be preferred to subject the conductive substrate to a movement during or after coating with the coating composition provided in step (B). Such a movement may be shaking, vibrating, rattling, rocking, etc. Vibration can be achieved in step (C), for example, by ultrasonic treatment.
[0048] In particular when using porous conductive substrates, it is preferred that the coating in step (C) fills the pores and / or cavities of the conductive substrate. It is further preferred to remove the supernatant coating composition, i.e. the coating composition that has not flowed into the pores and / or cavities, before subjecting the coated substrate to step (D). Removal can be achieved by skimming, for example using a doctor blade. Skimming can also contribute to improved filling of the pores and / or cavities. The thickness of the coated conductive substrate is therefore essentially the same compared to the uncoated conductive substrate.
[0049] In the method of the present invention, in step (D), it is preferred to compress the conductive substrate coated with the coating composition obtained after step (C). Such compression can further reduce the process time. In addition to the economic advantage, compression also reduces the risk of the binder spreading on the surface of the electrode active material and optional additives. Compression can also control the residual porosity of the final electrode.
[0050] In step (D), it is particularly preferred to apply a compression in the range of 10 to 70% of the thickness of the coated conductive substrate obtained after step (C). The degree of compression can be selected to adjust the desired residual porosity of the final electrode.
[0051] In step (D) of the method of the invention, the temperature applied by heating is preferably set to be above the Tg of the binder, in particular the polymeric binder. In particular, if compression is applied in step (D), the applied temperature is also preferably the Tm of the binder, in particular the polymeric binder. Preferably, the applied temperature is between the Tg and Tm of the binder, in particular, if compression is applied in step (D). It is preferred to be below the Tm of the binder in the range of 1°C to 50°C, more preferably in the range of 2°C to 30°C, even more preferably in the range of 3°C to 20°C. For example, PVDF is a suitable polymeric binder with a Tm of 177°C. Thus, in the heating in step (D), it is preferred that the heating is applied to provide a temperature in the range of 127°C to 176°C, more preferably in the range of 147°C to 175°C, even more preferably in the range of 157°C to 174°C. In general, it is preferred to bring the temperature applied in step (D) close to the Tm of the binder. In this context, temperatures of 50°C, 30°C, or 20°C to below the Tm of the binder are particularly preferred. At temperatures close to the Tm of the binder, the binder is activated and binds the components of the coating composition together and to the conductive substrate. The closer the temperature is to the Tm of the binder, the more preferred it is, since it allows the process time of step (D) to be shorter, which provides economic advantages. If the temperature applied in step (D) is above the Tm, the binder melts. This can cause the binder to spread over the surface area of the electrode active material and the optional additives, such as carbon black. This can result in the electrode active material being covered with a film of the binder, which does not achieve a sufficient binding effect and can lead to poor electrode performance. Therefore, it is preferred that the application temperature is at least 1°C, at least 2°C, or at least 3°C lower than the Tm of the binder. A certain difference between the Tm and the application temperature confers more stability to the process and reduces the risk of accidental overheating, i.e. heating above the Tm. Some materials only have a Tg and do not have a Tm. For other materials, Tm is above the decomposition temperature (Tz). In any case, it is preferred that the temperature applied in step (D) is below Tz.Tz as indicated herein refers to the decomposition onset temperature determined by thermogravimetric analysis (TGA) under a protective gas atmosphere. It is therefore also preferred that the application temperature is between the Tg and Tz of the binder, preferably at least 10°C above Tg, more preferably at least 20°C above Tg, and even more preferably at least 30°C above Tg but still below Tz.
[0052] The heating and compression can be carried out one after the other. Alternatively, and more preferably, the heating and compression in step (D) of the method of the present invention are carried out simultaneously, i.e., the hot coated conductive substrate is compressed. This can be accomplished by hot pressing or by calendering the coated conductive substrate with a heated calender. The hot press or calender roll is heated to the application temperature. Heat is transferred by contacting the hot press or calender roll with the coated substrate, either by direct contact or through a support such as those mentioned above.
[0053] Step (D) of the method of the present invention can be carried out using a variety of heating devices. Suitable heating devices include induction furnaces, infrared furnaces, high temperature ceramic heating elements and / or zone furnaces, such as conveyor furnaces. The heating device may suitably be a continuous furnace or a batch furnace.
[0054] The heating in step (D) can also be carried out without compression, i.e. by heating the coated conductive substrate using a heating device as described above. In such a case, it is possible to apply a temperature above the Tm of the binder. In such a case, the applied temperature is preferably set to be 50°C, more preferably 30°C, even more preferably 20°C below the Tm of the binder, and preferably at most 20°C, more preferably at most 10°C, even more preferably at most 5°C above the Tm of the binder. Due to the absence of external pressure, the processing time is longer compared to when step (D) includes the application of such pressure. Although the compression-free process allows good control over the process, the overall stability of the final electrode observed is higher when some compression is applied.
[0055] Furthermore, the present application relates to an electrode comprising a conductive substrate dry coated with a coating composition comprising an electrode active material and a polymeric binder. Dry coating of the conductive substrate allows its manufacture without evaporation of the solvent and allows for a higher volume density of the electrode active material since no evaporation channels or bubbles are involved. Electrodes coated with the dispersion have a structure determined by the evaporation of the solvent, such as evaporation channels and bubbles. Such structures are not present in electrodes resulting from the methods described herein that utilize dry coating.
[0056] Preferably, the electrode of the present invention is obtainable by the method for producing an electrode as described above and in the claims.
[0057] The present invention further relates to a dry coating composition comprising a conductive substrate, an electrode active material, and a polymeric binder, the dry coating being a free-flowing powder. As the coating composition is a dry coating composition, it is essentially free of water and solvents.
[0058] In contrast to other dry coating compositions, the amount of conductivity enhancing additives, such as silver wires, carbon nanotubes, conductive carbon black, or conductive binders (which may also include graphite for conductivity enhancement in the case of the cathode) can be kept to a minimum or even avoided altogether. In this context, the content of conductivity enhancing additives is preferably 10% by weight or less, more preferably 8% by weight or less, and even more preferably 6% by weight or less, based on the total weight of the dry coating composition.
[0059] The dry coating composition of the present invention is preferably free of conductive polymer binders, carbon nanotubes, and silver nanowires, i.e., the total amount thereof is preferably 0.1 wt % or less. Such conductive polymer binders are rather expensive and, as mentioned above, are not necessary when the dry coating composition is used in combination with a porous conductive substrate.
[0060] Furthermore, the present invention relates to a battery comprising an electrode according to the invention.
[0061] It will be understood that the details set forth above for the conductive substrate and coating composition in the context of the method of the present invention apply correspondingly to the electrodes and coating compositions of the present invention.
[0062] The invention will now be described in more detail, by way of example only, with reference to the accompanying drawings and figures, in which: [Brief description of the drawings]
[0063] [Figure 1] FIG. 1 is an exemplary schematic diagram of a process according to the present invention. [Diagram 2] 1 is a graph showing the capacitance versus voltage of the electrodes of Example 1 and Comparative Example 1. [Diagram 3] 1 is a graph showing the cycle behavior of the electrodes of Example 1 and Comparative Example 1. [Figure 4]1 is a scanning electrode microscope image of an electrode according to Example 1. [Diagram 5] 1 is a scanning electrode microscope image of an electrode according to Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0064] FIG. 1 shows a schematic diagram of the preparation of an electrode 1 according to the method of the present invention. First, in step (A), a conductive substrate 10 having a three-dimensional structure is prepared. In FIG. 1, a cross-sectional view of the conductive substrate is shown, and the black lines indicate a network of fibers. These fibers may be metal fibers, carbon fibers, or carbon nanotubes that impart high electrical conductivity. A coating composition 12 is prepared in step (B), which includes an electrode active material and a binder, as well as optional additives, such as graphite and carbon black if the electrode active material is not present. In step (C), the conductive substrate 10 is coated with the coating composition to obtain a coated conductive substrate 14, on whose surface a part of the coating composition is present as a supernatant 16. To improve the filling of the pores of the conductive substrate 10, the conductive substrate 10 may be subjected to a movement such as vibration when being filled with the coating composition 12. The supernatant 16 is removed using a doctor blade 18. The coated conductive substrate 14 is then hot calendered between two hot calender rolls 20 to heat and compress the conductive substrate in one step to obtain a fabricated electrode. This corresponds to step (D) of the present invention.
[0065] Figure 2 shows the voltage vs. capacity of two electrodes. One electrode was produced using the dry coating method according to the invention, as further described below under Example 1. The data corresponding to the electrode according to the invention are shown by the black line. Another electrode (Comparative Example 1) was also produced using the same conductive substrate and a coating composition, the only difference being that it was applied in the form of a slurry, which was applied conventionally using a dispersion technique and then evaporated. This electrode corresponds to Comparative Example 1. The data corresponding to the electrode according to Comparative Example 1 are shown by the grey line. In Figure 3 the cycling behavior of the electrode of Figure 2 is shown. As can be easily seen, the performance behavior is similar.
[0066] FIG. 4 shows a scanning electrode microscopy of the electrode of Example 1. Its conductive substrate consists of copper fibers, in particular CuSi3 fibers containing 3% by weight of silicon, sintered together to form a conductive network. In the microscope image, the metal fibers 100 can be seen as the grey areas in the center. The graphite particles 102 appear as dark plates, while the binder 104 can be seen as white flakes due to the inclusion of conductive carbon black in the binder 104. In FIG. 4, only the graphite particles 102 and some of the binder particles 104 are labeled with reference numbers.
[0067] FIG. 5 shows a scanning electrode microscopy of the electrode of Example 5. Its conductive substrate consists of aluminum fibers sintered together to form a conductive network. In the microscopic image, the metal fibers 100 can be seen as smooth gray areas in the left part of the micrograph. The binder 104 can be seen as white flakes because it contains conductive carbon black. The electrode active material NCA 106 can be seen as light gray spherical particles. The graphite particles 102 can also be seen as dark plates. In FIG. 5, only the graphite particles 102, the binder particles 104, and some of the NCA particles 106 are labeled with reference numbers.
[0068] The present invention will now be further described with reference to examples.
[0069] In Examples 1 and 2, a network of copper fibers was used as the conductive substrate. In Examples 3 to 5, a network of aluminum fibers was used as the conductive substrate. The network of metal fibers can be obtained as described in WO 2020 / 016240 A1.
[0070] The coating composition for preparing electrodes from these networks of metal fibers was obtained by preparing the components shown in Table 1 in powder form and mixing them thoroughly in a mortar. Additive 1 is included in the binder. The coating composition was dry, i.e. essentially free of water and other solvents, and in the form of a free-flowing powder. The composition shown in Table 1 is suitable for coating 2D electrodes, i.e. metal foils, and 3D electrodes, i.e. porous conductive substrates, for example in the form of a network of metal fibers. The use of the same coating composition for both types of conductive substrates allows a better comparison. Nevertheless, in the case of 3D electrodes it is possible to use much lower amounts of binders and additives, or even none at all.
[0071] [Table 1]
[0072] In Table 1, the values in brackets indicate the weight percent based on 100% by weight of the total coating composition. Graphite is synthetic graphite powder less than 20 μm (Sigma Aldrich (Art. Nr. 282863)) and is calcined graphite. PVDF is poly(vinylidene fluoride) (Alfa Aesar (Art. Nr. 44080)). Super-P is conductive carbon black (Alfa Aesar, (Art. Nr. H30253)). LTO is lithium titanate (Targray (Art. Nr. SLTO102)), NMC622 is lithium nickel manganese cobalt oxide (Targray (Art. Nr. SNMC03006)) and NCA is lithium nickel cobalt aluminum oxide (MTI Corp. (Art. Nr. Lib-LNCA810)).
[0073] The conductive substrate was placed on a siliconized paper as a support to prevent the coating composition in the form of a free-flowing powder from flowing through the conductive substrate. For each example, the corresponding coating composition shown in Table 1 was sprinkled on the corresponding conductive substrate. The supernatant coating composition was then removed by a doctor blade. The coated conductive substrate samples were then subjected to two different types of heat treatments, as shown below.
[0074] The first type of heat treatment: Each sample of Examples 1-5 was heated in an oven to 170°C for 60 minutes. After cooling to room temperature, the samples were compressed by calendaring to reduce their thickness by approximately 50%. The thickness of the samples after calendaring compression ranged from 150μm to 200μm.
[0075] The second type of heat treatment: Each sample of Examples 1 to 5 was hot calendered at a calender roll temperature of 160° C. and a speed of 5 m / min. In the calendering, 50% compression of the sample was achieved so that the thickness of the sample after compression by the calendering was in the range of 150 μm to 200 μm.
[0076] After the heat treatment, disks with a diameter of 14 mm were punched out from the samples. Both types of heat treatment were successful in preparing electrodes, but it was found that the second type of heat treatment (hot calendering) resulted in better adhesion between the electrode active material and the conductive substrate. Only a small amount of electrode active material was lost when punching out the disks. In contrast, when the first type of heat treatment (compression at room temperature after heating without compression) was applied, loss of electrode active material when punching out the disks could be observed at the edges of the punched disks, but no active material was lost in the center of the disks, i.e., again an acceptable electrode was obtained. The 14 mm disks were tested against metallic lithium in coin cells.
[0077] In addition, as Comparative Example 1, the metal fiber network used in Example 1 as a conductive substrate was coated by a general wet coating process. In the wet coating process, the coating composition used in Examples 1 to 5 was dispersed in acetone. An electrode was prepared as described in WO 2020 / 016240 A1.
[0078] The electrodes of Example 1 and Comparative Example 1 showed comparable performance in terms of capacity and cycling behavior, as shown by the measurements shown in Figures 2 and 3. Also, in terms of mechanical stability, the performance of these electrodes was comparable, especially when the second type of heat treatment (hot calendering) was applied. Nevertheless, the electrodes of Example 1 can be prepared using solvent-free dry coating, i.e., no solvents harmful to health and / or the environment are required to prepare the electrodes of Example 1. Furthermore, since the electrodes of the present invention are prepared using dry coating, it is possible to obtain a higher volumetric filling factor of the electrodes, since no solvent evaporation is required and, as a result, there are no channels and bubbles due to solvent evaporation.
[0079] The electrodes of Examples 1-5 also showed improved stability compared to two-dimensional electrodes, as observed for the three-dimensional electrodes disclosed in WO 2020 / 016240A1. Thus, when the electrodes of Examples 1-5 were folded (90° to one side, 180° to the other side, then returned to the original position), only 1-3 wt.% of the electrode active material was lost. The loss observed in Example 1 did not increase with a reduced amount of binder, as in Example 2. Also, the electrodes of Examples 3-5 show a comparably low active material loss when subjected to folding. In contrast, when two-dimensional electrodes (copper or aluminum foil as conductive substrate) were subjected to the same folding, the electrode active material peeled off from the conductive substrate, resulting in loss of electrode functionality. [Explanation of symbols]
[0080] 1 electrode 10 Conductive base material 12 Coating Composition 14 Coated conductive substrates 16 Supernatant 18 Doctor Blade 20 Calendar Rolls 100 Metal Fibers 102 Graphite particles 104 Binder 106 NMC particles
Claims
1. A method for producing an electrode (1), comprising the steps of: A step (A) of preparing a conductive substrate (10); providing a coating composition (12) comprising an electrode active material and optionally a binder (104), said coating composition (12) being a free-flowing powder; A step (C) of coating the conductive substrate (10) prepared in the step (A) with the coating composition (12) prepared in the step (B); (D) heating the coated conductive substrate (14) obtained in step (C) and, optionally, compressing the coated conductive substrate (14) by calendering or the like; A method for producing an electrode (1), comprising:
2. The method of claim 1 , wherein the conductive substrate (10) is a porous conductive substrate.
3. The method of claim 1 or 2, wherein the conductive substrate (10) comprises a plurality of metal fibers (100) forming a network of metal fibers (100).
4. The method of claim 3 , wherein the metal fibers (100) are in direct contact with each other.
5. The method according to claim 1 or 2, wherein the thickness of the conductive substrate (10) is 200 μm or more, more preferably 500 μm or more, even more preferably 550 μm or more, even more preferably 600 μm or more, even more preferably 750 μm or more, even more preferably 1000 μm or more, even more preferably 1500 μm or more, even more preferably 3000 μm or more, and most preferably 5000 μm or more.
6. 3. The method of claim 1 or 2, wherein the step (B) of preparing a coating composition (12) comprises mixing the electrode active material, a polymeric binder (104), and optionally carbon black to obtain the coating composition as a free-flowing powder.
7. The method of claim 1 or 2, wherein the electrode active material comprises calcined graphite (102), in particular calcined graphite (102) essentially free of surface hydroxide groups.
8. The method of claim 1 or 2, wherein step (D) further comprises compressing the coated conductive substrate (14).
9. In step (D), the coated conductive substrate (14) is subjected to hot pressing, in particular calendering, The heating is (i) set to a temperature above the Tg of the binder but below the Tm of the binder, in particular set to a temperature in the range of at most 50° C., more preferably at most 30° C., even more preferably at most 20° C. below the Tm of the binder; and / or 9. The method of claim 8, wherein the heating is (ii) set to a temperature above the Tg of the binder but below the Tz of the binder, in particular the heating is set to a temperature at least 10° C. above the Tg, more preferably at least 20° C. above the Tg, even more preferably at least 30° C. above the Tg but below the Tz.
10. An electrode (1), comprising a coated conductive substrate (14), the coated conductive substrate (14) being dry coated with a coating composition (12) comprising an electrode active material and a polymeric binder.
11. 11. An electrode (1) according to claim 10, obtainable by the method according to claim 1 or 2.
12. A dry coating composition (12) for preparing an electrode (1) according to claim 10 and / or for use in the method according to claim 1 or 2, comprising an electrode active material and a polymeric binder (104), the dry coating composition (12) being a free-flowing powder.
13. 13. The dry coating composition (12) according to claim 12, wherein the content of the conductivity improving additive in the dry coating composition (12) is 10 wt.-% or less, in particular 8 wt.-% or less, or 6 wt.-% or less, based on the total weight of the dry coating composition.
14. A battery comprising an electrode (1) according to claim 10.
15. 15. An electrical circuit comprising the battery of claim 14.